ACG Clinical Guidelines: Prevention, Diagnosis, and Treatment of Clostridioides difficile Infections - Kelly, Colleen R.; Fischer, Monika; Allegretti, Jessica R.; LaPlante, Kerry; Stewart, David B.; Limketkai, Berkeley N.; Stollman, Neil H. (The American journal of gastroenterology, 2021)
Clostridioides difficile infection occurs when the bacterium produces toxin that causes diarrhea and inflammation of the colon. These guidelines indicate the preferred approach to the management of adults with C. difficile infection and represent the official practice recommendations of the American College of Gastroenterology. The scientific evidence for these guidelines was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation process. In instances where the evidence was not appropriate for Grading of Recommendations Assessment, Development, and Evaluation but there was consensus of significant clinical merit, key concept statements were developed using expert consensus. These guidelines are meant to be broadly applicable and should be viewed as the preferred, but not the only, approach to clinical scenarios.